Inverted repeats in the monkeypox virus genome are hot spots for mutation - Dobrovolná, Michaela; Brázda, Václav; Warner, Emily F; Bidula, Stefan (Journal of medical virology, 2023)
The current monkeypox virus (MPXV) strain differs from the strain arising in 2018 by 50+ single nucleotide polymorphisms (SNPs) and is mutating much faster than expected. The cytidine deaminase apolipoprotein B messenger RNA editing enzyme, catalytic subunit B (APOBEC3) was hypothesized to be driving this increased mutation. APOBEC has recently been identified to preferentially mutate cruciform DNA secondary structures formed by inverted repeats (IRs). IRs were recently identified as hot spots for mutation in severe acute respiratory syndrome coronavirus 2, and we aimed to identify whether IRs were also hot spots for mutation within MPXV genomes. We found that MPXV genomes were replete with IR sequences. Of the 50+ SNPs identified in the 2022 outbreak strain, 63.9% of these were found to have arisen within IR regions in the 2018 reference strain (MT903344.1). Notably, IR sequences found in the 2018 reference strain were significantly lost over time, with an average of 32.5% of these sequences being conserved in the 2022 MPXV genomes. This evidence was highly indicative that mutations were arising within IRs. This data provides further support to the hypothesis that APOBEC may be driving MPXV mutation and highlights the necessity for greater surveillance of IRs of MPXV genomes to detect new mutations.
Keywords: mutation; APOBEC; evolution; inverted repeats; Mutation; mutace; lidé; virus opičích neštovic; monkeypox; Humans; Monkeypox virus; COVID-19; SARS-CoV-2